Near Infrared Light Triggered Photo/Immuno-Therapy Toward Cancers - Xu, Xiaoxue; Lu, Hongxu; Lee, Ruda (Frontiers in Bioengineering and Biotechnology, 2020)
Nanomaterials-based phototherapies, such as photothermal therapy (PTT), photodynamic therapy (PDT) and photoimunotherapy (PIT) exhibit strong efficacy, minimal invasion and negligible side effects in tumor treatment. The near-infrared (NIR) phototherapies have received specific attention due to the high penetration depth in the biological tissues, less toxic to biological tissues and low dose of light radiation. Mediated via the novel NIR-responsive nanomaterials, the synergistic effects can be achieved from PTT and PDT to the immunotherapy to achieve precision medicine and prevent recurrence and metastasis. In addition to cancer cells apoptosis from the heat and reactive oxygen species, PTT and PDT can trigger immune responses. The antitumor effects can be enhanced by immune checkpoint blockage therapy. This review will discuss the mechanisms and applications of synergistic NIR-triggered photo-/immune-therapy for cancer treatment based on the types of nanomaterials and their structures. Furthermore, the challenges, potential solutions and future directions of NIR-triggered nanoparticle development for anticancer immunotherapy will be briefly discussed. The ultimate goal is to stimulate better strategies for combined phototherapeutic modalities via nanomaterial design and architecture, and thus to enhance the efficacy of cancer immunotherapy for clinical application transformation.